Ato‐Gal4 fly lines for gene function analysis: Eya is required in late progenitors for eye morphogenesis. Issue 6 (10th June 2015) - Yu, Linlin; Zhou, Qingxiang; Pignoni, Francesca
Summary The Gal4/UAS system is one of the most powerful tools for the study of cellular and developmental processes in Drosophila. Gal4 drivers can be used to induce targeted expression of dominant‐negative and dominant‐active proteins, histological markers, activity sensors, gene‐specific dsRNAs, modulators of cell survival or proliferation, and other reagents. Here, we describe novel atonal‐Gal4 lines that contain regions of the regulatory DNA of atonal, the proneural gene for photoreceptors, stretch receptors, auditory organ, and some olfactory sensilla. During neurogenesis, the atonal gene is expressed at a critical juncture, a time of transition from progenitor cell to developing neuron. Thus, these lines are particularly well suited for the study of the transcription factors and signaling molecules orchestrating this critical transition. To demonstrate their usefulness, we focus on two visual organs, the eye and the Bolwig. We demonstrate the induction of predicted eye phenotypes when expressing the dominant‐negative EGF receptor or a dsRNA against Notch in the developing eye disc. In another example, we show the deletion of the Bolwig's organ using the proapoptotic factor Hid. Finally, we investigate the function of the eye specification factor Eyes absent or Eya in late retinal progenitors, shortly before they begin morphogenesis. We show that Eya is still required in these late progenitors to promote eye formation, and show failure to induce the target gene atonal and consequent lack of neuron formation. genesis 53:347–355, 2015. © 2015 Wiley Periodicals, Inc.